2010
DOI: 10.1080/10942910802120139
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Efficacy of Mulberry (Morus IndicaL.) Leaves Extract and Powder in Edible Oil

Abstract: The antioxidant activity of mulberry (Morus Indica L.) leaves was evaluated in rice bran oil (RBO). The oil was subjected to accelerated oxidation at 100° C for 5 days and heat treatment at 180°C for 1 h. In order to examine its potential antioxidant activity, the oxidative stability of the oils was evaluated by employing peroxide value (PV), radical scavenging activity (RSA), thiobarbituric acid reactive substances assay (TBARS), and percent free fatty acids (FFA). Mulberry in two forms viz: the methanolic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 20 publications
(18 reference statements)
0
11
1
Order By: Relevance
“…Mulberry leaves have shown strong antioxidant properties in rice bran oil and inhibition of oxidative deterioration of oil was observed to be even better than synthetic antioxidants [23]. Some reports have attributed these salient features to the many phytochemical constituents present in mulberry leaves [24].…”
Section: Introductionmentioning
confidence: 99%
“…Mulberry leaves have shown strong antioxidant properties in rice bran oil and inhibition of oxidative deterioration of oil was observed to be even better than synthetic antioxidants [23]. Some reports have attributed these salient features to the many phytochemical constituents present in mulberry leaves [24].…”
Section: Introductionmentioning
confidence: 99%
“…15 The methods applied in this study considered the antioxidant properties of the mulberry extract as determined by different group testing methods. 16 It has been reported that mulberry contains a lot of bioactive compound, polysaccharides, but in this study did not extracted on a Box-Behnken design, polysacharide function isolation. It is well known that the biological functions including antioxidant activity of polysaccharides are intimately related to their structure features such as chemical components, molecular weight, monosaccharide composition and glycosidic linkage.…”
Section: Discussionmentioning
confidence: 78%
“…Excessive formation of free radicals accelerated the oxidation of lipids in foods and induced severe damage to adjacent biomolecules. [29,30] DPPH assay evaluated the radical scavenging ability of antioxidants. Under ethanol solution, antioxidants could interact with the DPPH radical and transfer an electron or hydrogen atom to the DPPH radical, thus neutralizing its free radical character.…”
Section: Antioxidant Activities Of Aadf Melanin and Aafb Melaninmentioning
confidence: 99%